INT J ENV SCI ED 2016
DOI: 10.12973/ijese.2016.349a
|View full text |Cite
|
Sign up to set email alerts
|

School Principals’ Reflective Leadership Skills through the Eyes of Science and Mathematics Teachers

Abstract: Reflective leadership plays a key role in successfully maintaining the operation in organizations and in achieving their far and near objectives. In order to enable this success in school organizations, each employee in the school should make an effort for development and effective operation of the school organization. A reflective school leader is effective in enabling and sustaining this success by utilizing their reflective leadership traits. The aim of this research is to determine the reflective leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To improve the quality of instruction, teachers with the guidance of their supervisors must engage in the process of reflection which will allow teachers to explore their teaching practices, evaluate performance of students, and apply strategies or methods that will increase the students' academic performance (Disu, 2017). Reflection is a process that involves deep thinking about action and experience that may influence conceptual knowledge, ethical and moral belief, and future courses of action (Ersozlu, 2016;Weiss & Weiss, 2001;Yip, 2006). Daudelin (as cited by Ersozlu, 2016) states that a person who undergoes reflection must take a step back and think critically the past and present events to acquire the right knowledge, skills, and attitude.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To improve the quality of instruction, teachers with the guidance of their supervisors must engage in the process of reflection which will allow teachers to explore their teaching practices, evaluate performance of students, and apply strategies or methods that will increase the students' academic performance (Disu, 2017). Reflection is a process that involves deep thinking about action and experience that may influence conceptual knowledge, ethical and moral belief, and future courses of action (Ersozlu, 2016;Weiss & Weiss, 2001;Yip, 2006). Daudelin (as cited by Ersozlu, 2016) states that a person who undergoes reflection must take a step back and think critically the past and present events to acquire the right knowledge, skills, and attitude.…”
Section: Introductionmentioning
confidence: 99%
“…Reflection is a process that involves deep thinking about action and experience that may influence conceptual knowledge, ethical and moral belief, and future courses of action (Ersozlu, 2016;Weiss & Weiss, 2001;Yip, 2006). Daudelin (as cited by Ersozlu, 2016) states that a person who undergoes reflection must take a step back and think critically the past and present events to acquire the right knowledge, skills, and attitude. Lunenburg and Ornstein indicated that reflection enables the teacher and the supervisor to think about their own work by planning, evaluating, and improving their professional practice (Ersozlu, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflection has been used at various levels in the education sector. For example, reflection has been an important source of learning and improvement at the pedagogical level (Loughran, 2010b), at the student self-regulation level (Bonner & Chen, 2019;Cowie, 2005;Dayal et al, 2017;Hattie & Timperley, 2007;Klenowski, 2002), and at the leadership level (Ersozlu, 2016). The power of reflection at the classroom teaching level offers teachers the opportunity to identify their own strengths and weaknesses in light of the criteria and standards for teaching evaluation.…”
Section: Introductionmentioning
confidence: 99%